Oral Pemphigus Vulgaris: A case report - Baral, Radha; Ojha, Bidhata; Bajracharya, Dipshikha (Journal of Chitwan Medical College, 2020)
Pemphigus vulgaris is an autoimmune blistering disease clinically presenting as vesicles, bullae and erosion on the skin and mucous membrane. Histopathologically, it is characterized by acantholysis and supra basilar split. The underlying mechanism causing intra epithelial split in pemphigus vulgaris is binding of IgG autoantibodies to desmoglin 3 which belongs to a transmembrane glycoprotein adhesion molecule. Here we present a case of 27 years old male patient suffering from pemphigus vulgaris. This Case report highlights the importance of detailed case history, thorough clinical examination and appropriate investigation to reach a diagnosis of vesiculobullous lesion.